2021
DOI: 10.1038/s41594-021-00559-9
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptors form different complexes with UNC93B1

Abstract: The multipass transmembrane protein UNC93B1 is critical for the proper trafficking and function of many members of the Toll-like receptor (TLR) family of innate immune receptors. A new study reports two structures of UNC93B1 in complex with full-length TLR3 or TLR7 and sheds light on how this single chaperone may differentially interact with and regulate the function of individual TLRs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Endosomal trafficking of TLRs is critical for their downstream signaling ( Lee and Barton, 2014 ). Endosomal nucleic acid–sensing TLR3, TLR7, TLR8, and TLR9 must be delivered to the endocytic compartments, facilitated by the chaperone Unc-93 Homolog B1 (UNC93B1), and undergo proteolytic cleavage by cathepsins and asparagine endopeptidase to produce functional receptors, which are able to transmit signals to downstream molecules, upon ligand binding ( Ewald et al, 2011 ; Rael and Barton, 2021 ; Tabeta et al, 2006 ). Recent studies have indicated that both TLR3 and TLR9, but not TLR7, have to be released from UNC93B1 in the endolysosomal compartment to enable binding to their ligands ( Majer et al, 2019b ).…”
Section: Introductionmentioning
confidence: 99%
“…Endosomal trafficking of TLRs is critical for their downstream signaling ( Lee and Barton, 2014 ). Endosomal nucleic acid–sensing TLR3, TLR7, TLR8, and TLR9 must be delivered to the endocytic compartments, facilitated by the chaperone Unc-93 Homolog B1 (UNC93B1), and undergo proteolytic cleavage by cathepsins and asparagine endopeptidase to produce functional receptors, which are able to transmit signals to downstream molecules, upon ligand binding ( Ewald et al, 2011 ; Rael and Barton, 2021 ; Tabeta et al, 2006 ). Recent studies have indicated that both TLR3 and TLR9, but not TLR7, have to be released from UNC93B1 in the endolysosomal compartment to enable binding to their ligands ( Majer et al, 2019b ).…”
Section: Introductionmentioning
confidence: 99%